2018
DOI: 10.3390/app8112201
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Efficacy of Commercially Available Essential Oils Tested Against Drug-Resistant Gram-Positive Pathogens

Abstract: The potential antibacterial activity of basil (Ocimum basilicum), chamomile (Matricaria chamomilla), origanum (Thymus capitatus), tea tree (Melaleuca alternifolia) and thyme (Thymus vulgaris) essential oils, was investigated against 29 Gram-positive bacterial strains isolated from wastewater treatment plants, clinical samples (n = 25) and American Type Culture Collection (ATCC) reference strains (n = 4). Wild bacterial strains included methicillin-resistant Staphylococcus aureus (n = 16) and vancomycin-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 51 publications
5
18
1
1
Order By: Relevance
“…Carvacrol was generally found to be main constituent of oregano EO, with very good antibacterial effect [21,49]. In this study, from all the oils evaluated, thyme EO presented the lowest MIC against E. faecalis, as previously reported [49][50][51]. In concordance with other findings [52], our HPLC analysis showed thymol, para-cymene, gamma-terpinene and linalool as main bioactive constituents of thyme EO.…”
Section: Discussionsupporting
confidence: 91%
“…Carvacrol was generally found to be main constituent of oregano EO, with very good antibacterial effect [21,49]. In this study, from all the oils evaluated, thyme EO presented the lowest MIC against E. faecalis, as previously reported [49][50][51]. In concordance with other findings [52], our HPLC analysis showed thymol, para-cymene, gamma-terpinene and linalool as main bioactive constituents of thyme EO.…”
Section: Discussionsupporting
confidence: 91%
“…These results are corroborated by other studies that found high antimicrobial activity against several bacterial species, including Staphylococcus spp. [11,12,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…They are widely employed in cosmetics industry, perfumery, and aromatherapy [8]. The antimicrobial properties of several EOs and their constituents have been studied mainly through assays against bacterial and fungal strains of different genera, including staphylococci [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the anti-staphylococcal activity of O. vulgare and T. vulgaris EOs thanks to their main components carvacrol and thymol [ 36 , 47 , 48 , 49 , 50 ]. However, EOs obtained also from other botanical species were shown to be effective against staphylococci.…”
Section: Bacterial Infectionsmentioning
confidence: 99%